The Synergistic Effect Of Tannins And Iodide Ions On The Corrosion Inhibition Of Mild Steel In Corrosive Media - Adam, Mohd Ridhwan (2014)
The inhibition effect of mangrove tannin (MgT), mimosa tannin (MmT) and chestnut tannin (CnT) on the corrosion behaviour of mild steel in 0.5 M HCl, 0.25 M H2SO4 and 3.5 % NaCl solutions was studied using weight loss, potentiodynamic polarisation and electrochemical impedance spectroscopy (EIS) techniques. The results from all techniques studied showed that MgT gave satisfactory inhibition efficiencies on mild steel. The performance of MgT was further enhanced when iodide ions were added into the corrosive media containing this inhibitor, indicating the occurrence of synergism between these two compounds. In the weight loss analyses, the inhibition efficiencies for all three tannins have been increased from 38-85 % to 82-97 % when iodide ions were introduced into the corrosive media containing these inhibitors. The inhibition efficiencies for all three tannins were enhanced from 47-89 % to 83-94 % when combined with iodide ions in the potentiodynamic polarisation measurements. In the EIS measurements, the inhibition efficiencies for all three tannins were further increased from 69-84 % to 80-92 % when these tannins were synergised by the iodide ions. The inhibition efficiencies obtained from the weight loss and electrochemical measurements were in good agreement. Potentiodynamic polarisation studies clearly revealed that MgT behaved as mixed-type inhibitor with predominant anodic effectiveness. The Nyquist plots obtained from the EIS analyses showed that the inhibition process was mainly controlled by a charge transfer process.